Cognitive Behavioral Counseling Modeling Technique Procedures to Increase Student Learning Motivation and Concentration - I Kadek Sudiarsana; I Ketut Dharsana; Kadek Suranata; Ni Ketut Suarni; Luh Putu Sri Lestari (Bisma The Journal of Counseling, 2023)
Students' low motivation and concentration can be seen from their lack of focus in participating in class learning. This has an impact on reducing student learning outcomes. One effort that can be made to overcome this problem is by providing cognitive behavioral counseling services to students. This research aims to analyze the procedures for implementing cognitive behavioral counseling modeling techniques to increase student learning motivation and concentration as well as analyzing the suitability of the validity of the contents of the cognitive behavioral counseling manual modeling techniques. This research includes development research using the Four-D research model. The subjects involved in this research were 3 competent experts in the field of Guidance Counseling and Psychology, 5 Guidance Counseling Teachers, and 34 junior high school students as subjects in a limited trial. Data collection was carried out using a questionnaire method with a research instrument in the form of a guidebook product validity instrument. Data analysis was carried out using the Lawshe formula, while hypothesis testing used MANOVA. The research results showed that the CVR value per item obtained a score of 1 (CVR > 0) and the results of the CVI analysis obtained a score of 1 (CVI > 0). Meanwhile, the results of the hypothesis test obtained a sig value. 0.000 (< 0.05). It can be concluded that the inovation  product has a very high content validity value and it is proven that the cognitive behavioral modeling technique counseling guide is effective in increasing students' learning motivation and concentration. This research has implications for improving the quality of student learning through increasing learning motivation and concentration.